Cross-Antenna Polyphase Interleaving and Inversion scheme to reduce the PAPR of MIMO-FBMC/OQAM system - Mounira Laabidi; Ridha Boualleguee (International Journal of Electronics and Telecommunications)
Filter Bank Multi-Carrier with Offset Quadrature Amplitude symbol mapping called as FBMC/OQAM is presented as a potential successor of Orthogonal Frequency Division Multiplexing OFDM. Combined with Multiple-Input Multiple- Output (MIMO), MIMO-FBMC/OQAM is a promising modulation scheme for high performance broadband wireless communications. However, one major drawback of MIMO-FBMC/OQAM is the high peak-to-average power ratio (PAPR) of the output signals. Latinovic et al. Proposed a PAPR reduction method called Polyphase Interleaving and Inversion (PII) for MIMOOFDM systems under the use of the space-frequency block coding (SFBC) [1]. In this investigation, we suggest two schemes called Cross Antenna Polyphase Interleaving and Inversion 1 and 2 (CAPII1/(CAPII2) PAPR reduction schemes for Space Frequency Block Coding MIMO-FBMC systems which consequently utilizes additional degrees of freedom by employing multiple antennas and generating more patterns leading to more signal candidates to transmit, while requiring a limited amount of side information. The simulation results show that both the proposed CAPII schemes experience remarkable gain in PAPR.